2017
DOI: 10.1140/epjc/s10052-017-4800-2
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological model from the holographic equipartition law with a modified Rényi entropy

Abstract: Cosmological equations were recently derived by Padmanabhan from the expansion of cosmic space due to the difference between the degrees of freedom on the surface and in the bulk in a region of space. In this study, a modified Rényi entropy is applied to Padmanabhan's 'holographic equipartition law', by regarding the Bekenstein-Hawking entropy as a nonextensive Tsallis entropy and using a logarithmic formula of the original Rényi entropy. Consequently, the acceleration equation including an extra driving term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 131 publications
(235 reference statements)
4
139
0
Order By: Relevance
“…The results indicate that, compared with the Newtonian regime, the gravitational potential energy of the cloud is decreased when EUP is valid, leading to growth in the Jeans mass. It has been argued that since gravity is a long-range interaction, one may use the Rényi entropy formalism to study the gravitational systems (Komatsu 2017 14) is valid in both the EUP and Rényi frameworks. Hence, the EUP results, obtained in this paper, are also available in the framework of Rényi entropy (one just needs to replace 4β in the results of second section with δπ to obtain the corresponding results in the Rényi formalism).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that, compared with the Newtonian regime, the gravitational potential energy of the cloud is decreased when EUP is valid, leading to growth in the Jeans mass. It has been argued that since gravity is a long-range interaction, one may use the Rényi entropy formalism to study the gravitational systems (Komatsu 2017 14) is valid in both the EUP and Rényi frameworks. Hence, the EUP results, obtained in this paper, are also available in the framework of Rényi entropy (one just needs to replace 4β in the results of second section with δπ to obtain the corresponding results in the Rényi formalism).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the explicit form of the expression determining γ , it is the Rényi entropy formula for black holes [as defined in (22)] which arises. In another recent work [56], our Tsallis-Rényi model has been considered in a cosmological setup describing the difference between the degrees of freedom on the surface and in the bulk in a closed region of space. It has been found that the corresponding Padmanabhan's "holographic equipartition law" [57] can result an effective cosmological constant in the model.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we assume an arbitrary entropy on the horizon, extending the previous works [29,30] (in which particular entropies were used). In the present study, we apply the arbitrary entropy to the holographic equipartition model, in order to universally examine thermodynamic constraints on an extra driving term in cosmological equations for a flat Friedmann-Robertson-Walker (FRW) universe at late times.…”
Section: Introductionmentioning
confidence: 99%